VISUALIZATION ANALYSIS OF LOCAL SKINCARE BRAND DATA USING GOOGLE DATA STUDIO - Diah Ayu Novitasari (Jurnal Scientia, 2023)
The development of the Indonesian economy, which is getting better and rising after the Covid-19 pandemic, has encouraged domestic entrepreneurs to produce higher quality domestic products. The proud slogan uses domestic products as if they don't wear out with time and shine even more. One of the increasingly viral and quality local products is skincare. These local skincare products have skyrocketed along with the awareness level of Indonesian people who are increasingly literate about the importance of taking care of their faces and body. Some skincare brands that are of public concern are the samples in this study. The purpose of this study is to visualize and mapping the development of skincare brands on websites and Instagram based on several things using Google Studio data. Some of these things include total visitors, pages per visit, bounce rate and average visit, total followers, engagement rate, like rate, comment rate. The results show that Somethinc is the champion in terms of total visitors to the website. The highest page per visit is the Avoskin brand. The lowest bounce rate is also owned by the Avoskin brand. The highest average visit is Mineral Botanica. The most total followers on Instagram are Scarlett Whitening. The most liked rate on Instagram is Avoskin. The best comment rate is For Skins Sake. The best engagement rate is Avoskin. The hope of this research is that it can be used as a reference and one of the reasons for local skincare brands in developing their product marketing on their website and Instagram